Recuso-me ! Ditos e escritos de Maria Lacerda de Moura - Miranda, Jussara Valéria de (2006)
The purpose of this dissertation is discuss some conceptions present in Maria Lacerda Moura´s thought (1887-1945), among them the consciousness objection and the woman´s independence . An activist during the 20´s and 30´s decades, Maria Lacerda has declared herself a selfish, anti-social, anticlerical and anti-fascist person, follower of free love, of aware motherhood and of woman´s independence rom both man and the capital. In the first chapter on this work, I discuss the consciousness objection notion in the author´s writings. I intend to analyse the lacerdian thought setting it against the libertarian ideas. Through this movement, I inquire the issues discussed by her, in order to comprehend her world ´s view and changing predictions. In the second chapter, I try to focus on the women´s images built in that period., as well as the author´s ideas about the woman´s independence . The documenting used in this research can be found in Arquivo Edgard Leuenroth in UNICAMP, in the archives of Centro de Cultura Social from São Paulo, in the Biblioteca Pública Municipal de São Paulo and in the Dicionário-Biográfico do(s) Arnarquismo(s) no Brasil , presented as a report paper research to FAPEMIG. The documents are books, articles, magazines and leaflets from Maria Lacerda de Moura, a rebel strongly influenced by the libertarian thoughts and committed to the construction of new life paradigma by her discoursive action.